Midgut malrotation complicated by small bowel obstruction in an 80-year-old woman: A case report. (2019) - Haqqani, Maha; Seetharaman, Mani; Teo, Richard; Adkisson, Christian; Nessen, Michelle; Dauer, Marc; Kim, Peter K.
Highlights: Intestinal malrotation results from anomalies in embryological midgut rotation. Malrotation usually presents early in life, with rare cases reported in adulthood. Ladd procedure remains the mainstay of definitive treatment. Radiologic findings have a role in early detection and correction of malrotation. Abstract: Introduction: Midgut malrotation results from abnormalities in the 270-degree counterclockwise rotation of the midgut around the axis of the superior mesenteric artery during embryological development, and classically presents early in life with symptoms of intestinal obstruction. Nevertheless, adult cases have occasionally been reported. Presentation of case: An 80-year-old female with no surgical history was brought to our emergency department for acutely altered mental status. On exam, her abdomen was distended and diffusely tender to palpation. Computed tomography (CT) scan of the abdomen and pelvis showed a dilated loop of jejunum with evidence of mesenteric twist concerning for closed-loop small bowel obstruction. The patient was taken for exploratory laparotomy and was found to have Ladd bands and other findings suggestive of intestinal malrotation. A Ladd procedure was performed and the patient remained under observation. She experienced intermittent abdominal distension and bilious nasogastric tube output, but subsequent CT scans revealed no evidence of obstruction. She was discharged following clinical improvement and ability to tolerate a diet. Discussion: Malrotation of the small bowel exists on a spectrum depending on the embryologic stage during which anomalous rotation occurs. Classic findings on CT imaging (including abnormal mesenteric vasculature, right-sided duodenojejunal junction, whirlpool signs, and left-sided ascending colon) can provide clues to the existence of malrotation. Conclusion: Although malrotation is rare in adults, clinical and radiologic findings play an important role in the correct diagnosis of adult malrotation for appropriate and timely intervention.